Photoaligned liquid-crystal lens with a single low-voltage electrode - Muravsky, A.A.; Agabekov, V.E.; Tolstik, A.L.; Mahilny, U.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The simple design of liquid-crystal lenses with single electrode and operation
voltage below 5 V is highly desired. We offer a new type of photoaligned liquid-crystal
lens, where the refractive gradient is created by voltage application due to the patterned
twist angle gradient. In this paper, we present our calculations and experimental data.